الشيخ محمد بن عمر نووي الجاوي: حياته الذاتية والعلمية - Ehsan Ur Rehman; Dr. Muhammad Iqbal Khan (الآفاق اسلامی و تحقیقی مجلہ)
Sheikh Muhammad bin Umaranawi al-Jawi (Banteni), a scholar and mystic. His title "Nawawi" is said to be derived from one of the famous scholars. He was born in 1230 AH (1814 CE) in the village of Tenara, Banten, Indonesia. He grew up in a household of knowledge, as his father was a scholar and an official in the Dutch colonial government. This environment allowed Muhammad Nawawi to begin his studies at an early age. He learned the basics of sciences such as theology, jurisprudence, grammar, and exegesis from his father, alongside his brothers Tamim and Ahmad, during his childhood. Sheikh Nawawi was Ash'ari in creed, Shafi'i in school of thought, and Sufi in practice. In the field of Sufism, he followed the path of Imam al-Ghazali, and evidence of this is Nawawi's own explanation of al-Ghazali's book Bidayat al-Hidaya. Sheikh had great determination and was never known to tire. Reading, writing on various topics, and research were his constant pursuits. He authored a large number of scholarly works on different subjects, which can be divided into two categories: A: Books he authored on specific topics. B: Books on various subjects. This article deals with his life and scholarly contribution to Islamic disciplines.